A value-based definition of success in adaptive port planning: a case study of the Port of Isafjordur in Iceland - Majid Eskafi; Reza Fazeli; Ali Dastgheib; Poonam Taneja; Gudmundur F. Ulfarsson; Ragnheidur I. Thorarinsdottir; Gunnar Stefansson
Abstract Multiple stakeholders with a wide range of objectives are engaged in a port system. Ports themselves are faced with many uncertainties in this volatile world. To meet stakeholder objectives and deal with uncertainties, adaptive port planning is increasingly being acknowledged. This method offers robust planning, and thereby, a sustainable and flexible port may be developed. The planning process starts with defining success in terms of the specific objectives of stakeholders during the projected lifetime of the port. In the present work, an integrated framework to reach a consensus on the definition of success, involving stakeholders with different influences, stakes and objectives, is presented. The framework synthesises the problem structuring method with stakeholder analysis and combines these with fuzzy logic to support decision-makers in formulating a definition of success in the planning process. Our framework is applied to the Port of Isafjordur, the third busiest port of call for cruise ships in Iceland. Values of stakeholders about port planning were structured around the value-focussed thinking method to identify stakeholder objectives. The highest level of agreement on the objectives, which is viewed here as success in port planning, was revealed by the fuzzy multi-attribute group decision-making method. Success was defined, prioritising an increase in competitiveness among other planning objectives, such as effective and efficient use of land, increasing safety and security, increasing hinterland connectivity, increasing financial performance, better environmental implications, flexibility creation and increasing positive economic and social impacts. Decision-making process, Adaptive port planning, Definition of success, Value-focussed thinking, Iceland